Day 100 Peripheral Blood Absolute Lymphocyte/Monocyte Ratio and Survival in Classical Hodgkin's Lymphoma Postautologous Peripheral Blood Hematopoietic Stem Cell Transplantation. (24th April 2013) - Porrata, Luis F.; Inwards, David J.; Ansell, Stephen M.; Micallef, Ivana N.; Johnston, Patrick B.; Hogan, William J.; Markovic, Svetomir N.
Abstract : Day 100 prognostic factors of postautologous peripheral blood hematopoietic stem cell transplantation (APBHSCT) to predict clinical outcome in classical Hodgkin lymphoma (cHL) patients have not been evaluated. Thus, we studied if the day 100 peripheral blood absolute lymphocyte/monocyte ratio (Day 100 ALC/AMC) affects clinical outcomes by landmark analysis from day 100 post-APBHSCT. Only cHL patients achieving a complete remission at day 100 post-APBHSCT were studied. From 2000 to 2010, 131 cHL consecutive patients qualified for the study. The median followup from day 100 was 4.1 years (range: 0.2–12.3 years). Patients with a Day 100 ALC/AMC ≥ 1.3 experienced superior overall survival (OS) and progression-free survival (PFS) compared with Day 100 ALC/AMC < 1.3 (from day 100: OS, median not reached versus 2.8 years; 5 years OS rates of 93% (95% CI, 83%–97%) versus 35% (95% CI, 19%–51%), resp., P < 0.0001 ; from day 100: PFS, median not reached versus 1.2 years; 5 years PFS rates of 79% (95% CI, 69%–86%) versus 27% (95% CI, 14%–45%), resp., P < 0.0001 ). Day ALC/AMC ratio was an independent predictor for OS and PFS. Thus, Day 100 ALC/AMC ratio is a simple biomarker that can help to assess clinical outcomes from day 100 post-APBHSCT in cHL patients.